A new biodegradable elastomeric polyester amide for soft tissue engineering applications - Essa, Abdulrahman (2018)
Elastomeric scaffolds play an important role in the field of soft tissue engineering, and recently, studies investigating different medical applications for these scaffolds have been increasing rapidly. New thermoset bioelastomers have demonstrated promising applications for myocardial, vascular and nerve tissue engineering. Nevertheless, these elastomers have several disadvantages, including the toxicity of the degradation products of the polyester family and the poor solubility of the poly(ester amide) (PEAs) family in the most commonly used polar and nonpolar solvents, which restricts fabrication. Therefore, this PhD project aims to develop a novel biodegradable and biocompatible elastomer to overcome the disadvantages of currently available PEA elastomers, such as the poor solubility of the PEA pre-polymer and the limitations of its mechanical properties, in order to create an elastomer which is similar to protein-based polymers, thus allowing for wider use in soft tissue engineering applications.